Trifoliate hybrids as rootstocks for sweet orange ’Valência’ - Junior, Jorgino Pompeu; Blumer, Silvia (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to evaluate the productivity and agronomic traits of ’Valência’ sweet orange tree budded onto trifoliate (Poncirus trifoliata) hybrids rootstocks. Fruit production, total soluble solids production per plant, canopy production efficiency and dimensions of ’Valência’ sweet orange trees budded onto 13 trifoliate hybrids, culivated under nonirrigation conditions, were evaluated in periods ranging from three to eight years. Plants were also visually evaluated for symptoms of citrus blight and tristeza (Citrus tristeza virus) diseases, and the dot immunobinding assay (DIBA) test was used for detecting blight disease before the development of its symptoms. Plants were eight years old at the evaluation beginning. Trees on ’Sunki’ x ’English’ citrandarin and ’Troyer’ citrange produced the highest cumulative yields in eight crops. In a three-year period, ’Sunki’ x ’English’’ and ’Troyer’ and ’Carrizo’ induced the highest fruit yields and soluble solids per tree. The citrentin ’Clementina’ x trifoliate, and the citrandarins ’Cleopatra’ x ’Swingle’ (715) and (1.614), ’Cleopatra’ x ’Rubidoux’ (1.600) and ’Cleopatra’ x ’Christian’ induced the formation of the smallest ’Valência’ trees with heights below 2.5 m. None of the trees showed symptoms of tristeza or blight disease. Trees on trangpur ’Cravo’ x ’Carrizo’ showed bud-union-ring symptom of incompatibility.